Brazil: Capital goods industry during the 2003-2008 boom and following the global crisis - Guilherme Riccioppo Magacho (CEPAL Review, 2016)
The capital goods industry is essential for technological development and long-term economic growth without external restrictions. After a long period of stagnation, investment growth resumed in Brazil in 2003 and brought renewed vigor to the capital goods industry. Nevertheless, the industry is very diverse, and some sectors have failed to meet rising demand where others have succeeded, namely those with high technological potential such as suppliers of machinery for the oil, mining and construction industries and makers of transportation and electrical generation and distribution equipment. Those sectors continued to expand even in the wake of the 2008 global crisis and have been barely touched by foreign competition.